Strategy of Islamic Religious Education Teachers in Increasing Student Learning Motivation - Sri Wahyuni; Sanchita Bhattacharya (Pascasarjana Pendidikan Agama Islam Institut KH. Abdul Chalim Mojokerto, 2021)
The purpose of the article was to describe and analyze strategies of Islamic Religious Education (IRE) Teachers in Improving Students' Learning Motivation in Madrasah Aliyah (MA) Class X Hikmatul Amanah. The type of research used is qualitative with a case study approach. Data collection is done by observation, interviews, documentation. Data analysis used the Miles and Huberman method, namely by reducing, presenting, and certifying data. To test the validity of the data by testing credibility, transferability, dependability, and confirmability. The results of this article show 1) IRE teachers at Hikmatul Amanah Mojokerto Islamic School have implemented strategies and methods that are in accordance with the applicable curriculum at the school. However, there are still shortcomings where the teacher lacks varied and boring strategies and methods in the learning process so that students are less motivated to learn pie subjects 2) the inhibiting factor of the teacher's strategy in increasing student motivation to learn is the lack of communication between teachers and parents, the lack of learning media, the family environment, and the school environment can also be an obstacle for teachers during the teaching and learning process. The supporting factors for the teacher's strategy are from the students themselves, how they feel a strong desire and have high aspirations so they are motivated to learn and receive support in the form of attention, rewards, and punishment, praise from family, teachers, and the environment.